1988
DOI: 10.1177/002580248802800209
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement in Those Who Have Killed

Abstract: The background to complicated grieving is discussed with particular reference to individuals who were responsible for the death of a loved one. Aspects of management are presented, and a review of criminal statistics demonstrates the likely scale of this type of bereavement reaction on a national basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…He described how the therapist can be overwhelmed by the enormity of the suffering and sense of helplessness of the family, and the importance of having a frame of reference to enable the therapist to ''hang in'' with the family's pain. Fraser (1988) addressed the issue of treatment of depressive illness and abnormal grief reactions in perpetrators of homicide not derived from psychotic illness. He reviewed the literature and drew on clinical experience.…”
Section: Introductionmentioning
confidence: 99%
“…He described how the therapist can be overwhelmed by the enormity of the suffering and sense of helplessness of the family, and the importance of having a frame of reference to enable the therapist to ''hang in'' with the family's pain. Fraser (1988) addressed the issue of treatment of depressive illness and abnormal grief reactions in perpetrators of homicide not derived from psychotic illness. He reviewed the literature and drew on clinical experience.…”
Section: Introductionmentioning
confidence: 99%
“…Case studies suggest that PTSD symptoms are more pronounced if the offenders have been emotionally attached to their victim (Harry and Resnick, 1986;Rynearson, 1984). A high proportion of people who kill experience abnormal grief reactions, which share some of the symptoms of PTSD, with a preponderance of guilt (Fraser, 1988). In their series of three patients, Harry and Resnick found that perpetrators of homicide may still suffer PTSD symptoms many years after the homicide.…”
mentioning
confidence: 99%